Contrastive Analysis on Ilokano and English Personal Pronouns - Tabula, Rommel; Salasac, Constante (JPAIR Multidisciplinary Research, 2015)
Pairwise scientific description of foreign and native languages can predict and describe the patterns that may cause learning difficulties. This study explored the descriptions of Ilokano personal pronouns in parallel with English and the contrastive structure in these two languages in which personal pronouns occur. Using descriptive-ethnographic research design, data were gathered from an informant who substantiated the categorized personal pronouns obtained from reliable materials. Results showed that Ilokano personal pronouns are structurally independent and incorporated into other parts of speech as suffixes. Contrastive analysis further found that Ilokano personal pronouns present special characteristics which differ significantly to their English counterparts. Firstly, Ilokano personal pronouns provide speakers with respectful forms of address in various contexts which is absent in English. Secondly, Ilokano pronoun suffixes -ak, -ko, and -k are applied to all tenses and moods while English personal pronouns take the free morpheme in all cases. Thirdly, the Ilokano subject affects the verb form and the object suffix whereas English verb structure remains unchanged except for the third person singular and the object pronoun. Lastly, pronouns are common to all genders in Ilokano while this matters in English. Thus, Ilokano and English personal pronouns manifest parallel characteristics but have distinct differences in some aspects.